2020
DOI: 10.1039/d0ra04408c
|View full text |Cite
|
Sign up to set email alerts
|

Marine natural products from sponges (Porifera) of the order Dictyoceratida (2013 to 2019); a promising source for drug discovery

Abstract: Marine organisms have been considered an interesting target for the discovery of different classes of secondary natural products with wide-ranging biological activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 67 publications
1
25
0
Order By: Relevance
“…Sponges represent an important reservoir of bioactive marine natural compounds. Abdelaleem et al [ 35 ] reported the number of isolated bioactive compounds in a taxon of the order Demospongiae between 2013 and 2019, showing that 195 new compounds and 189 known compounds were isolated. These compounds have been reported to have a broad range of bioactivities, such as antimicrobial, cytotoxic, antioxidant, antiviral, anti-allergic, anti-parasitic, and anti-inflammatory [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sponges represent an important reservoir of bioactive marine natural compounds. Abdelaleem et al [ 35 ] reported the number of isolated bioactive compounds in a taxon of the order Demospongiae between 2013 and 2019, showing that 195 new compounds and 189 known compounds were isolated. These compounds have been reported to have a broad range of bioactivities, such as antimicrobial, cytotoxic, antioxidant, antiviral, anti-allergic, anti-parasitic, and anti-inflammatory [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…By following the procedure described in our previous study [18], the crude product yielded from the ethyl acetate extraction of the lyophilized bodies of the soft coral S. manaarensis was chromatographed to produce DHS at a high purity, as proven by 1 H and 13 C NMR spectra (Supplementary Figures S2 and S3). The inhibitor, NAC (Sigma-Aldrich, St. Louis, MO, USA) [28,[52][53][54], was pretreated before DHS treatment.…”
Section: Preparation Of Dhs and Inhibitorsmentioning
confidence: 99%
“…Marine natural products exhibit diverse functions to avoid damage from bacterial, fungal, protozoal, tuberculosis, and viral infections [6][7][8][9][10]. Many extracts and compounds derived from marine natural products such as sponges and soft corals also show anticancer effects [8,9,[11][12][13][14][15]. These extracts warrant further development as anticancer drugs for oral cancer therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike synthetic compounds, which are subjected to a series of structural modifications during the course of a drug discovery/development project to achieve improved drug-like or lead-like properties, natural products are produced and modified in nature over a long period of time throughout evolution. Hence, the biologically-relevant ‘chemical space’ of these products from nature is recognised to be markedly greater than in synthetic compound libraries [ 6 ]; thus, natural compounds have potential to interact with a variety of biological targets [ 7 , 8 , 9 , 10 , 11 ]. In addition, the ‘metabolite-likeness’ of natural products (i.e., their ability to act as substrates in one or more cellular systems) can facilitate the delivery of such compounds to their ultimate active sites via their binding to transporters [ 6 ].…”
Section: Introductionmentioning
confidence: 99%